2015
DOI: 10.1105/tpc.15.00733
|View full text |Cite
|
Sign up to set email alerts
|

Job Sharing in the Endomembrane System: Vacuolar Acidification Requires the Combined Activity of V-ATPase and V-PPase

Abstract: The presence of a large central vacuole is one of the hallmarks of a prototypical plant cell, and the multiple functions of this compartment require massive fluxes of molecules across its limiting membrane, the tonoplast. Transport is assumed to be energized by the membrane potential and the proton gradient established by the combined activity of two proton pumps, the vacuolar H + -pyrophosphatase (V-PPase) and the vacuolar H + -ATPase (V-ATPase). Exactly how labor is divided between these two enzymes has rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
98
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(107 citation statements)
references
References 70 publications
(91 reference statements)
8
98
1
Order By: Relevance
“…A recent study indicated that vacuolar acidification is collectively contributed by the TGN/ EE-associated and the tonoplast-associated V-ATPases (40). Thus, the effect of VHA-A loss of function could be from the TGN/EE and the vacuoles (39).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study indicated that vacuolar acidification is collectively contributed by the TGN/ EE-associated and the tonoplast-associated V-ATPases (40). Thus, the effect of VHA-A loss of function could be from the TGN/EE and the vacuoles (39).…”
Section: Discussionmentioning
confidence: 99%
“…In fugu5-1, a knockout of the PP i -ase AtAVP1, the vacuolar pH was increased by 0.25 units compared with the wildtype pH of 5.8 (Ferjani et al, 2011). The triple mutant vha2 3 vha3 3 avp1 shows that these two kinds of proton pumps present an additive function only in some cell types (Kriegel et al, 2015). In petunia (Petunia hybrida) petals, the vacuolar membrane also contains ATPases of the P-type, the type found at the plasma membrane (Verweij et al, 2008;Faraco et al, 2014), but there is no report for such a function in Arabidopsis guard cells.…”
Section: Vacuolar Ph During Stomatal Movementmentioning
confidence: 98%
“…Hence, part of the proton gradient necessary for stomatal opening must be generated elsewhere. It has been suggested that vacuolar acidity originates during vacuolar biogenesis and, thus, relies on other acidic compartments, such as the transGolgi network/early endosome (Schumacher, 2014;Kriegel et al, 2015). The det3 mutant, a knockout of the trans-Golgi network/early endosome-localized V-type ATPase, however, shows impaired stomatal closure (Allen et al, 2000;Brüx et al, 2008), but stomatal opening was not reported to be affected in this mutant.…”
Section: Vacuolar Ph During Stomatal Movementmentioning
confidence: 98%
See 1 more Smart Citation
“…The authors wondered whether the remaining proton gradient in the mutant was entirely due to V-PPase activity or whether other pumps contributed to vacuolar acidification. Now, Kriegel et al (2015) have dissected the contribution of V-ATPases and V-PPases to vacuolar acidification using a panel of Arabidopsis mutants. In addition to vha-a2 vha-a3, they obtained mutants lacking the tonoplast-localized K 1 -stimulated V-PPase (fugu5-1) and generated plants in which the K 1 -stimulated V-PPase was overexpressed in the vha-a2 vha-a3 background (UBQ:AVP1 vha-a2 vha-a3) and a triple mutant lacking both V-ATPases and the V-PPase (fugu5-1 vha-a2 vha-a3).…”
mentioning
confidence: 99%